2. The effects of KEM CON ONG and KEM TRI BONG creams on doxorubicin-induced skin ulcer in rats - Anh, Pham Thi Van; Huy, Vu Quang; Loan, Nguyen Thi Thanh; Trang, Tran Thuy; Giang, Nguyen Kim; Nga, Nguyen Thi Quynh; Tung, Tran Thanh (Tạp chí Nghiên cứu Y học, 2023)
The present study evaluated the effects of topical administration of KEM CON ONG and KEM TRI BONG creams on doxorubicin-induced skin ulcer, and their systemic toxicity in ulcerated rats. The skin lesions were induced by a single intradermal injection of 0.2ml doxorubicin 1 mg/0.5ml on the dorsal region. The ulcerated areas were covered topically with dimethyl sulfoxide, KEM CON ONG, or KEM TRI BONG twice a day for 28 days. The results indicated that KEM CON ONG and KEM TRI BONG significantly reduced the ulcer size, increased the hydroxyproline content in animals’ skin tissues, and improved the histopathological structure of skin tissues. No significant difference in the healing effect was observed between KEM CON ONG and KEM TRI BONG-treated ulcerated rats. Besides, our study demonstrated that topical administration of KEM CON ONG and KEM TRI BONG creams caused no significant change in the general status, hematological parameters, renal and hepatic functions. Additionally, they did not alter the histology of the liver and kidney in animals. In conclusion, the topical application of KEM CON ONG and KEM TRI BONG creams exerted healing effects on the ulcerated skin and did not cause systemic toxicity in a rat model.